ETNOMATEMATIKA PADA AKTIVITAS PEMBUATAN BATIK MOTIF TEMBAKAU DI RUMAH PRODUKSI BATIK NHORA PENGESTU AMBULU SEBAGAI BAHAN PAKET SOAL TES - Cahyanti, Endah Dwi (Kadikma, 2020)
Ethnomatematics is the science of mathematics practiced by a cultural group where the society has unconsciously applied the concept of mathematics. The purpose of this study is to describe ethnomatemics in the activity of making tobacco motifs and to produce test packages. This type of research is a qualitative research with an ethnographic approach. There are three subjects in this study, S1 as the maker of patterns / designs, color locking, and "nglorod", S2 as a dyeing and coloring, and S3 as the maker of batik cap. Data collection methods used are observation, interviews, and documentation. This research is focused on the tobacco making batik activity. The results of this study indicate the existence of ethnomatematics which includes activities: counting, measuring, and designing. Ethnomatematics in this study was made as a test package in the form of descriptive questions for even ninth grade students.